Pengaruh Leisure Benefit Terhadap Tingkat Kepuasan Pengunjung Milenial dalam Aktivitas Leisure and Recreation di Kebun Raya Bogor - Lengkong, Shara Chrisofia; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2021)
Millennials Are Happiness-Seeker. Millennials currently use their free time with fun, yet meaningful things. In the midst of the busy routine of life, someone has free time or Leisure time which is a period where that person no longer does activities or efforts to meet primary needs. One of the things that many millennial generations do today is recreation to visit tourist attractions. Bogor Botanical Gardens is suitable to be a place to escape from daily routines, the pressures of urban life or a place to escape from work because it has an atmosphere, scenery and air that suits the tastes of visitors, especially millennial generations who crave meaningful life because they can relax themselves. at the same time pleasing yourself but have a positive meaning for his life. Visitor satisfaction when visiting a tourist destination is the goal of every tourist destination manager. Given that the millennial generation is a very potential tourism consumer. Therefore, this research was conducted to determine Leisure and Recreation activities at the Bogor Botanical Gardens and the influence of Leisure Benefits on the satisfaction level of millennial visitors in carrying out these various activities. This research uses descriptive analysis. The type of research used in this research is explanatory research. The data collection method uses a survey method by distributing questionnaires via google form, where the questionnaire is distributed online to 100 millennial respondents who have visited Bogor Botanical Gardens. The results of this study are activities to fill spare time or Leisure and Recreation activities that can be done at the Bogor Botanical Gardens, including: Relaxation Activity; Entertainment Activity; and Personal Development Activity, and Questionnaire Results related to the influence of Leisure Benefits on visitor satisfaction at the Bogor Botanical Gardens, it can be seen that by carrying out Leisure and Recreation activities at the Bogor Botanical Gardens visitors get Benefits in terms of Physical Benefits; Psychological Benefit; and Social Benefits. Keyword: Leisure and Recreation, Leisure Benefit, Millennials, Bogor Botanical Garden I. PENDAHULUAN Setiap individu memiliki waktu luang atau Leisure Time diluar dari aktivitas untuk memenuhi kebutuhan primer. Leisure Time biasanya dimanfaatkan untuk bersantai, bersenang-senang, memulihkan kesehatan jasmani maupun rohani, menghilangkan penat dari rutinitas harian, mencari ketenangan dan pengalaman baru. Banyak hal yang dapat dilakukan seseorang untuk mengisi waktu luang antara lain dengan menjalankan hobi, berolahraga, mengunjungi keluarga dan kerabat, dan banyak aktivitas lainnya (Suryasih, dkk., 2019). Salah satunya yang banyak dilakukan oleh para generasi milenial saat ini adalah rekreasi mengunjungi tempat wisata, misalnya mengisi waktu luang diakhir pekan cukup dengan berkeliling ataupun duduk piknik di suatu tempat yang memiliki suasana lingkungan yang asri dikelilingi pepohonan rindang. Kota Bogor yang terkenal dengan sebutan “Kota Hijau” sudah terkenal sebagai destinasi wisata sejak lama. Pembangunan pariwisata di kota Bogor memiliki kaitan dengan kota Bandung dan beberapa daya tarik wisata di sekitarnya yang memiliki panorama alam indah dan sejuk. Pada tanggal 12-14 Januari 1957 di kota Bogor digelar Musyawarah Nasional